Phenotype and genotype analysis in patients with macular corneal dystrophy. Issue 11 (11th June 2014) - Nowinska, Anna K; Wylegala, Edward; Teper, Sławomir; Wróblewska-Czajka, Ewa; Aragona, Pasquale; Roszkowska, Anna M; Micali, Antonio; Pisani, Antonina; Puzzolo, Domenico
Abstract : Aim: The aim of this study was to analyse corneal morphological organisation and identify mutations in the carbohydrate sulfotransferase 6 gene ( CHST6 ) in patients with macular corneal dystrophy originating in a Polish population. Methods: Macular corneal dystrophy was diagnosed in 24 patients based on the slit-lamp exam, confocal microscopy, 1310 nm time domain and 840 nm spectral domain optical coherence tomography. 10 corneal buttons obtained from penetrating keratoplasty were processed for light microscopy. Genetic analysis of the CHST6 gene was performed, followed by a study of the sequencing results. Results: Highly reflective, diffuse corneal deposits and a general increase in reflectivity were revealed with optical coherence tomography and confocal microscopy. The deposits extended from the Bowman layer to the Descemet membrane and correlated with the Alcian blue-positive granular-filamentous material into and around the stromal keratocytes confirmed by structural analysis of the corneal buttons. The genetic analysis of the blood samples identified the following mutations and single nucleotide polymorphisms: novel P64L (heterozygous), Y110C (homozygous), R162G and L200R, and M1L (heterozygous and homozygous). Conclusions: Genetic mutation heterogeneity was revealed. No phenotype heterogeneity was revealed among patients with in vivo corneal morphology assessment or histological analysis.